Pelatihan Model Pemasaran Online untuk Wirausaha Tape di Desa Sukaraja Kecamatan Cikeusal, Serang - Anizir, Anizir; Wahyuddin, Wahyuddin; Subandi, Subandi; Kautsar, Ahmad; Deviyantoro, Deviyantoro (Empowerment, 2022)
Cikeusal sub-district is one of the sub-districts in Serang Regency, Banten Province, where most of the residents own cassava farming and cassava processing industry. One of the home industries for processing cassava in Cikeusal is the manufacture of tape made from real cassava and made directly by residents of Cikeusal. In addition to providing economic benefits, the production of cassava tape in the Cikeusal sub-district is the largest producer of cassava. Cassava tape production can reach 150-300 kg per day. The development of Information Technology (IT) has provided new opportunities for people's economic life. With these advances, there is no longer any limit in expanding market share in marketing a product or service that is owned. By taking advantage of this technological development, the people of Cikeusal village have expanded the marketing of tape to various regions. The method of service activities is carried out through training and assistance in the use of information technology related to marketing and sales. The results of this community service activity, by utilizing internet technology, have helped increase sales of tape cookies in Sukaraja Village, Cikeusal District, Serang Regency - Banten. Partners in this community service activity can optimize the sale of tape cookies by using internet media or online media.Kecamatan Cikeusal merupakan salah satu kecamatan di Kabupaten Serang Propinsi Banten yang sebagian besar warganya memiliki pertanian singkong dan industri pengolahan singkong. Salah satu home industry pengolahan singkong di Cikeusal adalah pembuatan tape yang terbuat dari singkong asli dan di buat langsung oleh warga Cikeusal. Selain memberikan keuntungan secara ekonomi, produksi tape singkong di kecamatan Cikeusal merupakan penghasil singkong terbesar. Produksi tape singkong bisa mencapai 150 – 300 kg per hari. Perkembangan Teknologi Informasi (TI) telah memberikan peluang baru bagi kehidupan perekonomian masyarakat. Dengan kemajuan tersebut sudah tidak ada lagi batasan dalam melakukan perluasan pangsa pasar dalam melakukan pemasaran suatu produk atau jasa yang dimiliki. Dengan memanfaatkan perkembangan teknologi ini, masyarakat desa Cikeusal melakukan perluasan pemasaran tape ke berbagai wilayah. Metode kegiatan pengabdian dilakukan melalui pelatihan dan pendampingan penggunaan teknologi informasi yang berkaitan dengan pemasaran dan penjualan. Hasil kegiatan pengabdian masyarakat ini, dengan memanfaatkan teknologi internet telah membantu meningkatkan penjualan tape cookies di Desa Sukaraja Kecamatan Cikeusal Kabupaten Serang – Banten.  Mitra dalam kegiatan pengabdian masyarakat ini dapat mengoptimalkan penjualan tape cookies dengan menggunakan media internet atau media online.